Cicatrices sin tiempo y espacio - Cortez, Linda María Concepción (Oltreoceano - Rivista sulle migrazioni, 2021)
Esta narrativa es un reflejo de la violencia en varios sentidos: un grupo étnico sometido históricamente, lo que los obliga a ocultar sus tradiciones y creencias; la cronología de un asesinato y la violencia intrafamiliar que conduce a la fatalidad y, finalmente, el acoso social. Todo confluye en una sociedad del siglo XXI. Timeless and Spaceless Scars This story is a reflection on different kinds of violence: a historically subdued ethnic group, forced to hide its traditions and beliefs; the account of a murder and of the domestic violence that leads to the casuality y; and, finally, social harassment. Everything comes together in the social context of the XXI century.